The ontological formula for eternal renewal of life in the Armenian fairy tale Barekendan and the singing game Tsapik, Tsapik, Tsirani - Seyranyan, Lilit B. (Имагология и компаративистика)
The article focuses on Armenian folk tales, children's folk singing games and ritual-mythical traditions, compared to their Russian, English, Albanian, and Czech equivalents. Armenian folklore is considered from the perspective of the relationship between life and death, this world and the afterlife, when ritual holidays, songs, and fairy tales become unique means of communication between the living and the dead. The authors compare Armenian fairy tale Kengane qandats tonn Astvats el chi qandil and Hovhannes Tumanyan's adaptation Barekendan with Russian Straw Maslenitsa and The Thieving Man, Albanian The Stupid Wife and the Czech fairy tale of the same name. The Armenian singing game Tsapik, Tsapik, Tsirani is compared to the Russian Ladushki, ladushki and the English Pat-a-cake. The authors use historical-comparative, mythocritical, and structural-semiotic methods to identify hidden sublayers of the folk-lore texts. The holidays and texts are explored in terms of food, sacrifice, ma-terial objects, ritual orgies, and mythological archetypes. As it has been shown, these semantic layers bear the imprint of both Christian and pre-Christian, that is, pagan folk beliefs. According to the authors, the entire semantic system of folklore symbols/images in the samples under study is based on the idea of eternal life cycle․ The interpretation employs specific signs-symbols. The compared fairy tales manifest a paradigm of sacrificial objects for the afterlife - oil and rice, bread, gruel, clothes, canvas, and money. The following units - grand-mother, grandfather, grandson, axe, food, tree (Tree of Life, World Tree, Family Tree), touching hands, and hare are considered in the semiotic system of the Armenian singing game under study. It is assumed that the grandmother stands for Maslenitsa, while the grandfather - for Great Lent, and, accordingly, the grandchild - for Easter. For the first time in the Armenian culturological discourse, the hare is identified with Easter, as a symbol of fertility and renewal of life. The interdisciplinary research combines scientific, ethnographic, theological, and literary perspectives. Verbal folklore is studies together with visual representations - illustrations of medieval Armenian books.